Restitution without Restoration? Exploring the Gap between the Perception and Implementation of Restitution. (December 2020) - Martin, Karin D.; Fowle, Matthew Z.
Restitution as a social practice can simultaneously have a punitive effect and add to a person's criminal justice debt load, while maintaining a reparative and therefore restorative component. We use principles of restorative justice to assess restitution as a concept and a practice, drawing on data from a survey experiment administered to a nationally representative sample ( n = 433). We find that the common and strongly preferred conception of restitution is "direct, " entailing a convicted person compensating a victim for quantifiable loss. Evidence from Victim Compensation Funds (VCFs) in all 50 states demonstrate the widespread use of "indirect" restitution, through which funds from various sources are distributed to qualifying victims. Broader trends in criminal justice policy related to the centering of the victim and a managerial approach to punishment help explain our findings. We conclude that the divergence between common conception and widespread practice indicates a need for a revised notion of restitution.